Mechanics and energetic analysis of rowing with big blades with randall foils - Cardoso, R.; Rios, M.; Carvalho, D.; Monteiro, A. S.; Soares, S.; Abraldes, J. A.; Gomes, B. B.; Vilas-Boas, J. P.; Fernandes, R. J. (International Journal of Sports Medicine, 2023)
Empirical observations support that the addition of a plastic strip - also known as Randall foils - on the top edge of a rowing blade improves rowing efficiency during the cycle propulsive phase. The aim of the current study was to analyze the effect of using big blades with and without Randall foils on rowing performance. Twenty experienced rowers performed two 90 s tethered rowing bouts (with and without Randall foils) to assess their impact on force production and physiologic variables. All tests were randomized and a repeated measure design was used to compare experimental conditions. Higher values of peak and mean peak forces (479.4±134.7 vs. 423.2±153.0, d=0.83 and 376.5±101.4 vs. 337.1±113.3 N, d=0.68), peak oxygen uptake (47.9±7.5 vs. 45.3±7.3 mL·kg-1·min-1, d=0.19), peak blood lactate concentration (7.9±1.6 vs. 6.9±1.7 mmol·L-1, d=0.16), blood lactate increasing speed (0.08±0.01 vs. 0.07±0.06 [(mmol·L-1)·s-1], d=0.27) and lactic anaerobic energy (27.4±7.9 vs. 23.4±8.1 kJ, d=0.23) were found for big blades with vs. without Randall foils, p<0.05. The current data suggest that the Randall foils can positively affect rowing performance.